Animal feed research in eastern and southern Africa; priorities and trends - Jutzi, S.C. (1993)
On the basis of an analysis of 2127 reports on animal feed research and development from seven national programmes in eastern and southern Africa, this paper intends to give a profile of animal feed research in the area since meaningful records have been available, to establish major trends in this research thrust in the transition from colonial to independent policy, and to discuss the main features of a feed research programme with a focus on livestock production in smallholder mixed farming.